2015
DOI: 10.1108/jd-09-2014-0137
|View full text |Cite
|
Sign up to set email alerts
|

Grey literature – grey sources? Nuancing the view on professional documentation

Abstract: Purpose -The purpose of this paper is to nuance the perception about professional documentation (a.k.a. "grey literature"), assuming perception of documentation being a cultural aspect of accessibility. Design/methodology/approach -The study explores variations within the archaeological report genre through a bibliometric analysis of source use. Source characteristics are explored as well as correlations between report authors and source originators. Statistical frequency distribution is complemented by a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…At the same time, the analysis indicated that the respondents tended to focus on their customary information sources and act within their habitual small information worlds (Burnett & Jaeger, 2008) or bounded "boxes" (Huvila, 2012). Even if the scopes of interest are not comparable, the two perspectives are reminiscent of the earlier highlighted fault lines in archaeological information production and use (including Börjesson's academic and administrative frames of references, Börjesson, 2015, andcolleagues, 2016, distinction of spatial, administrative and scientific information). In spite of the somewhat diverging interests in different types of information and some respondents' complaints of an information overflow, the respondents were rather unanimous in their interest in an early access to comprehensive and precise information about known archaeological sites and need to conduct further investigations.…”
Section: Information Usementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the analysis indicated that the respondents tended to focus on their customary information sources and act within their habitual small information worlds (Burnett & Jaeger, 2008) or bounded "boxes" (Huvila, 2012). Even if the scopes of interest are not comparable, the two perspectives are reminiscent of the earlier highlighted fault lines in archaeological information production and use (including Börjesson's academic and administrative frames of references, Börjesson, 2015, andcolleagues, 2016, distinction of spatial, administrative and scientific information). In spite of the somewhat diverging interests in different types of information and some respondents' complaints of an information overflow, the respondents were rather unanimous in their interest in an early access to comprehensive and precise information about known archaeological sites and need to conduct further investigations.…”
Section: Information Usementioning
confidence: 99%
“…They identified three distinct types of information in the process: administrative, spatial, and scientific, noting there is a lot of overlap between these categories. Börjesson (2015) has studied literature use in Swedish field reports from development-led archaeology projects. She concludes that there is latent variation between academically and administrative oriented frames of reference in the information use of report writers.…”
Section: Use and Usefulness Of Archaeological Informationmentioning
confidence: 99%
“…Despite the rich research on archaeological documentation only few studies focus specifically on the most common form of publication in archaeology: the DL archaeology report (Berggren and Burström, 2002;Börjesson, 2015;Seymour, 2009Seymour, , 2010a[1]. This study takes on DL archaeology as a case in an effort to add insight about this less studied form of archaeological documentation.…”
Section: Archaeology Documentationmentioning
confidence: 99%
“…Magnusson Staaf and Gustafsson, 2002;Riksantikvarieämbetet, 2012a). A less developed line of research concerns how archaeological documentation is regulated by legislations, regulations and praxis explicated in handbooks (Börjesson, 2015;Carver, 2009;cf. Lindh, 2015).…”
Section: Archaeological Documentationmentioning
confidence: 99%
See 1 more Smart Citation